THE NEEDS OF LEARNING RESOURCE MANAGEMENT FOR EDUCATION OF SCHOOLS UNDER PHRA NAKHON SI AYUTTHAYA PRIMARY EDUCATIONAL SERVICE AREA - Pumplub , Kamonphron; Boontham, Tongluck (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2021)
The aims of this research are to study: 1) the current state and desirable state of learning resource management for education under Phra Nakhon Si Ayutthaya education service area and 2) the needs of learning resource management for education of schools under Phra Nakhon Si Ayutthaya education service area. The sample group consisted of 366 administrators and primary teachers under Phra Nakhon Si Ayutthaya education service area chosen by stratified random sampling. The research instrument was a check- list questionnaire and the data were analyzed by using mean, standard deviation and priority needs analysis (PNIModified) The research results revealed that: 1) the current state of learning resource management for education as a whole was at the high level ( = 3.96, S.D.=0.76); 2) the desirable state of learning resource management for education was at the highest level ( = 4.54, S.D.=0.66) and 3) the needs of learning resource management for education respectively sorted descending order of the needs as follows: 1) evaluation of learning resource management (PNImodified =0.169);2) operation of learning resource (PNImodified =0.160); 3) development of learning resource (PNImodified =0.159) and 4) planning of learning resource management.